GAMBARAN PENGETAHUAN KEPALA KELUARGA TENTANG RUMAH SEHAT DI DESA ATEUK LAM URA KECAMATAN SIMPANG TIGA KABUPATEN ACEH BESAR - Nanda Sari; Ade Kiki Rieki (Jurnal Sains Riset, 2021)
Rumah Sehat, directly translated as Healthy House, is beneficial in achieving healthy family and clean environment around the house. Whereas the unhealthy house in cause of low life quality of physical and spiritual health which worsen the illnes riks and lessens people’s work productivity. The unhealthy house becomes the illnes source for its surroundings, not to mention when the a number of unhealthy house become a group of unhealthy houses. The aim of this reseacrh is to get the overview of the understanding of family head about healthy house at Desa Ateuk Lam Ura in Simpang Tiga Sub-districk in Aceh Besar Regency in 2018. The design of this reseacrh is descriptive-exprolative . The sample technique used in this reseacrh is ramdom sampling which is the technique of choosing the sample in random manner. This technique is consideret representative and it ends up to 60 family heads as the samples. The instrument used in this reseacrh is a questionnaire. This reseacrh was conducted from April 10 to April 13, 2018. The data analysis used in this reseacrh is univariate. The result of this research shows that the understanding of family heads about healthy house at Desa Ateuk Lam Ura in Simpang Tiga Sub-district in Aceh Besar Regency is at high category (36 respondents = 60,00%). The family understanding about the factors needed to be observed in creating a healthy house is in high category (34 respondents = 58,3%). In general, it can be concluded that the overview of family understanding about healthy house (Rumah Sehat) at Desa Ateuk Lam Ura in Simpang Tiga Sub-distric in Aceh Besar Regency in 2018 is in high category. Therefore, the head of Community Health Center in the area is suggested to improve people understanding and skill related to healthy house through training and counseling about health because society understanding is a complex thing to evaluate when it comes to impementation.by considering that public health science is a very complex science in its applicationKeywords: Family knowledge, Rumah Sehat